GPER-Induced ERK Signaling Decreases Cell Viability of Hepatocellular Carcinoma - Qiu, Yu-an; Xiong, Jianping; Fu, Qin; Dong, Yun; Liu, Manran; Peng, Meixi; Jin, Wenjian; Zhou, Lixia; Xu, Xue; Huang, Xianming; Fu, Airong; Xu, Guohui; et al. (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) is an aggressive malignancy with a poor prognosis. Effective biomarkers and specific therapeutic targets for HCC are therefore urgently needed. G protein-coupled estrogen receptor (GPER) plays a crucial role in numerous cancer types; however, its functions in HCC require further exploration. In the present study, we found a remarkable difference in GPER staining between tumor tissue (100/141, 70.9%) and matched nontumor tissue (27/30, 90.0%). Compared with the GPER-negative patients, the GPER-positive patients with HCC were closely associated with female sex, negative hepatitis B surface antigen, small tumor size, low serum alpha fetoprotein level, and longer overall survival. Treatment with GPER-specific agonist G1 led to the sustained and transient activation of the EGFR/ERK and EGFR/AKT signaling pathways, respectively, in the HCC cell lines HCCLM3 and SMMC-7721, which express high levels of GPER. Interestingly, G1-induced EGFR/ERK signaling, rather than EGFR/AKT signaling mediated by GPER, was involved in decreasing cell viability by blocking cell cycle progression, thereby promoting apoptosis and inhibiting cell growth. Clinical analysis indicated that simultaneous high expression of GPER and phosphorylated-ERK (p-ERK) predicted improved prognosis for HCC. Finally, the activation of GPER/ERK signaling remarkably suppressed tumor growth in an HCC xenograft model, and this result was consistent with the in vitro data. Our findings suggest that specific activation of the GPER/ERK axis may serve as a novel tumor-suppressive mechanism and that this axis could be a therapeutic target for HCC.